PILGRIMAGE TOURISM: ITS HISTORICAL AND PROGRESSIVE DEVELOPMENT AND CHARACTERISTICS (Scientific journal of the Fergana State University, 2026)
This article studies the historical development and specific features of one of the promising areas of tourism - pilgrimage tourism. Pilgrimage is studied as one of the means of spiritual development of people. The traditions of pilgrimage, recommendations on pilgrimage etiquette, empirical data on the development of pilgrimage as tourism and its main factors are analyzed. Also, strategies for the development of pilgrimage tourism, existing concepts on the classification of pilgrimage tourism are analyzed.